A programmable analog front-end with independent biasing technique for ECG signal acquisition. (June 2023) - Han, Wentao; Yu, Qi; Wu, Kejun; Zhang, Zhong; Li, Jing; Ning, Ning
Abstract: This paper presents a programmable low power and low noise analog front-end (AFE) for electrocardiogram (ECG) signal acquisition. A novel capacitor-coupled instrumentation amplifier (CCIA) features independent biasing technique and AC coupling to signal source is proposed. Independent biasing technique is capable of obtaining better noise performance and more stable static working point reducing the glitch of chopping. An AC coupling style helps suppress electrode DC offset and enhance input impedance with metal-oxide-metal capacitor array, which is symmetrical to the center to alleviate the mismatch of input capacitor enhancing system common mode rejection ratio (CMRR). The current steering technology (CST) and programmable feedback capacitors are utilized to achieve an area-efficient programmable low pass filter (PLPF) under PVT variations. Also, a charge buck after PLPF is introduced to strengthen the driving ability of AFE. To verify the proposed AFE structure, a prototype is designed in 0.13 μm standard CMOS process with a 1.2 V supply. Post-simulation results show that the input impedance reaches 1.4 GΩ under 50 Hz. The in-band white noise density and integrating noise are 48 nV/sqrt (Hz) and 0.6 μV, respectively. The obtained low pass corner of PLPF are 380 Hz, 451 Hz and 1 kHz. The CMRR and PSRR under montecarlo simulation are 93 dB and 77 dB, respectively. The power of whole AFE is 48 μW.